Integrative Bioinformatics Analysis to Identify Key Ferroptosis-Related Genes and Immune Infiltration in Aortic Aneurysm and Dissection: Implication of PTGS2 - An W; Luo J; Zhang C; Xiao Q (Journal of Inflammation Research)
Weiwei An,1,2 Jun Luo,3 Cheng Zhang,3 Qingzhong Xiao2 1Laboratory of Cardiovascular Science, Beijing Clinical Research Institute, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People’s Republic of China; 2William Harvey Research Institute, Barts and The London School of Medicine and Dentistry, Queen Mary University of London, London, EC1M 6BQ, United Kingdom; 3Department of Cardiothoracic Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of ChinaCorrespondence: Qingzhong Xiao, Centre for Clinical Pharmacology and Precision Medicine, William Harvey Research Institute, Barts and The London School of Medicine and Dentistry, Queen Mary University of London, Heart Centre Charterhouse Square, London, EC1M 6BQ, United Kingdom, Tel +44(0)2078826584, Email q.xiao@qmul.ac.uk Cheng Zhang, Department of Cardiothoracic Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of China, Email zhangcs05223@163.comBackground: Aortic aneurysm and dissection (AAD) represent a highly lethal cardiovascular condition. Ferroptosis has recently been implicated in AAD development and progression. However, ferroptosis-related genes (FRGs) have not been systematically identified and verified in AAD.Methods and Results: Seven human AAD datasets downloaded from Gene Expression Omnibus were analyzed, and 113 potential AAD-related FRGs were identified. Function enrichment analyses revealed that the FRGs were mainly associated with responses to chemical stress and cytokine signaling in the immune system. Protein–protein interaction network analyses identified 8 hub FRGs including EZH2, EGFR, HIF1A, IL6, PTGS2, MAPK1, IL1B and SRC. All these FRGs were significantly increased in patients with aortic aneurysm. Additionally, immune cell infiltration analyses revealed these FRGs were strongly correlated with the higher CD4+ Tem and macrophages fraction in AAD patients. Particularly, increased expression of PTGS2 in AAD patients was further validated using our newly collected clinical aortic specimens. Importantly, we found that PTGS2 knockdown could reduce the expression of MMP9 and MMP2 but increase GPX4 expression in macrophages. Conversely, while PTGS2 overexpression upregulated MMP9 and MMP2 expression but downregulated GPX4 expression, the regulatory effects of PTGS2 on these genes were largely blunted by ferroptosis inhibitors. Functionally, administration of celecoxib, a PTGS2-specific inhibitor, into mice significantly reduced β-aminopropionitrile-induced AAD development and progression.Conclusion: Through an integrative bioinformatics analysis, we have identified multiple key AAD-related FRGs including PTGS2. Functional studies also suggest a functional role of PTGS2 in ferroptosis and AAD development, offering novel insights into pathogenesis of human AAD.Keywords: aortic aneurysm and dissection, PTGS2, macrophage, ferroptosis, integrative bioinformatics analysis